2005
DOI: 10.1002/app.21672
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric behavior and properties of a cyanate ester containing dicyclopentadiene. I

Abstract: 2,6-Dimethyl phenol dicyclopentadiene dicyanate ester (DCPDCY) was synthesized through the reaction of 2,6-dimethyl phenol dicyclopentadiene novolac and cyanogen bromide. The proposed structure was confirmed by Fourier transform infrared, mass spectrometry, NMR spectrometry, and elemental analysis. DCPDCY was then cured by itself or cured with bisphenol A dicyanate ester (BADCY) to form triazine structures. The thermal properties of the cured DCPDCY resins were studied with differential scanning calorimetry, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…It was found that dependences of dielectric functions on frequency is sensitive to the ordered state due to more or less aligned macromolecules 45. Furthermore, It is reported46 that the dielectric constant could be increased by a decrease in free volume and by an increase in the polarization. The more efficient chain packing and a decrease in the free volume of the polymer raise the dielectric constant.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that dependences of dielectric functions on frequency is sensitive to the ordered state due to more or less aligned macromolecules 45. Furthermore, It is reported46 that the dielectric constant could be increased by a decrease in free volume and by an increase in the polarization. The more efficient chain packing and a decrease in the free volume of the polymer raise the dielectric constant.…”
Section: Resultsmentioning
confidence: 99%
“…A material with a low dielectric constant and loss will enhance the signal propagation speed and reduce the signal propagation loss,39 so the matrix for high‐frequency CCLs should have a low dielectric constant and loss.…”
Section: Resultsmentioning
confidence: 99%
“…A material with a low dielectric constant and loss will enhance the signal propagation speed and reduce the signal propagation loss, 39 so the matrix for high-frequency CCLs should have a low dielectric constant and loss. Figure 10 gives the dielectric constant of the cured BADCy-E and PPO-n/BADCy resins over a frequency range from 1 to 10 6 Hz.…”
Section: Dielectric Properties Of the Ppo-n/badcy Resinsmentioning
confidence: 99%
“…27 These results are in general agreement with other studies. 5, [16][17][18][19][20][28][29][30][31][32][33][34] The siliconcontaining analog of BADCy, bis(4-cyanatophenyl)dimethylsilane, or SiMCy, was synthesized in our laboratory according to a previously published procedure 27 that closely follows the original synthesis reported by Wright. 28,35 SiMCy exhibits a previously reported melting point of 338.2 ± 0.1 K, heat of fusion of 93 ± 1 J/g, and purity of 99.4 ± 0.1% after purification using chromatography.…”
Section: Methodsmentioning
confidence: 99%